Perception of poverty: A study on the non-social work students - Koustab Majumdar; Dipankar Chatterjee (Social Work & Society, 2020)
This study explored the non-social work student's perception of poverty and its causes and how cultural differences (rural and urban culture) influence the perception of poverty. Based on the qualitative research method, this study examined forty-two non-social work participants (students from rural development discipline) to (re)addressing the essential measures regarding institutional interventions on classroom teaching of poverty and curriculum development. This study revealed that the participants from rural culture perceived poverty through experiencing and observing the rural poor population. The urban participant's perception was based on urban poor population (living in the slum areas). The rural participants supported the structural and individualistic cause of poverty. Notably, the urban participants predominantly endorsed the structural, individualistic, and psychological cause as the cause of poverty. Moreover, this study found that the future commitment toward working with poverty affected people was stronger among rural participants than urban participants. It conclusively suggested that culture significantly influences the perception of an individual as the perceptual differences are inherently embedded in cultural experiences.